Prevalence and Impact of Seed-borne Fungal Pathogens on Soybean Quality in Telangana - Reshma, Shaik; Bharathi, Venuturla; Basha, Shaik Ameer; Rajanikanth, Panuganti (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was conducted during kharif, 2021 (June-September) at PJTAU, Hyderabad, Telangana, India to study the impact of seed-borne fungal pathogens on seed health and quality of soybean. Soybean seed samples were collected from various locations in Telangana state, and subjected to standard blotter and agar plate methods for the detection of seed-borne mycoflora associated with soybean. A total of eight fungal species, belonging to six genera, were detected, including Fusarium oxysporum, Fusarium semitectum, Macrophomina phaseolina, Colletotrichum truncatum, Curvularia spp., Aspergillus niger, Aspergillus flavus and Penicillium spp. using both the detection methods and among these, F. oxysporum and M. phaseolina were found to be predominant. The collected seed samples were also categorized into different grades based on visual observation, and the 100-seed weight was also recorded. To evaluate seed quality parameters, rolled paper towel method was employed. Among all the samples, the JS335 variety from Nizamabad district exhibited the highest total seed infection (49.02%), with the lowest germination (64.63%) and vigour index-I (1496). In contrast, the Basara variety from Adilabad district recorded the lowest seed infection (19.76%) with the highest germination (85.05%) and vigour index-I (3049). The results indicated a positive correlation between seed deformities, 100-seed weight and seed infection % in soybean, and these pathogenic seed-borne fungi were also found to be associated with reduced germination and other seed quality parameters.